2007
DOI: 10.1016/j.devcel.2007.03.018
|View full text |Cite
|
Sign up to set email alerts
|

SUN1 Is Required for Telomere Attachment to Nuclear Envelope and Gametogenesis in Mice

Abstract: Prior to the pairing and recombination between homologous chromosomes during meiosis, telomeres attach to the nuclear envelope and form a transient cluster. However, the protein factors mediating meiotic telomere attachment to the nuclear envelope and the requirement of this attachment for homolog pairing and synapsis have not been determined in animals. Here we show that the inner nuclear membrane protein SUN1 specifically associates with telomeres between the leptotene and diplotene stages during meiotic pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
460
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 379 publications
(488 citation statements)
references
References 42 publications
20
460
0
2
Order By: Relevance
“…Telomere-mediated movement along the nuclear envelope is crucial for homologous pairing and synapsis during meiosis (108). Meiotic telomeres carry a set of specific proteins such as SUN1, SUN2 and TERB1, which associate with telomeres between the leptotene and diplotene stages during meiotic prophase I (109,110). The telomere fusion during meiosis in our study could be associated with altered function of these telomere-associated proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Telomere-mediated movement along the nuclear envelope is crucial for homologous pairing and synapsis during meiosis (108). Meiotic telomeres carry a set of specific proteins such as SUN1, SUN2 and TERB1, which associate with telomeres between the leptotene and diplotene stages during meiotic prophase I (109,110). The telomere fusion during meiosis in our study could be associated with altered function of these telomere-associated proteins.…”
Section: Discussionmentioning
confidence: 99%
“…A crucial event promoting homolog synapsis is telomeremediated chromosome movement and the bouquet configuration of chromosomes, a process that depends on the NE proteins SUN/KASH and is disrupted in Sun1 knockout mice (Ding et al 2007). We examined the effect of Sun1 knockout on the process of homolog pairing.…”
Section: Homolog Association In Sun1 Knockoutmentioning
confidence: 99%
“…Arguably, chromosome movement that may promote alignment is thought to be crucial for homolog pairing (Voet et al 2003;Lee et al 2012;Boateng et al 2013;Lui et al 2013); however, it has been reported that 22%;25% of zygotenearrested Sun1 knockout spermatocytes form synapses (Ding et al 2007). Sun1 knockout spermatocytes lack overall chromosome movement (Shibuya et al 2014) but retain the ability to undergo homolog pairing (Fig.…”
Section: Telomere-driven Chromosome Movement Is Not Essential For Hommentioning
confidence: 99%
See 1 more Smart Citation
“…34 Likewise, meiotic bouquet formation also requires Sun1 and Sun2 in mammalian cells. 35,36 The interactions between yeast Mps3 and telomeres is likely to be mediated by a direct interaction with the Est1 component of the telomerase machinery. 37 Similarly, interactions between Mps3 and the telomerase machinery appear likely to regulate DSB localization to the periphery.…”
Section: Introductionmentioning
confidence: 99%